FROG Face Recognition via Multimedia Messaging. - Naval, Prospero C. (Philippine Computing Journal)
The challenging task of face recognition is addressed with the aim of developing an identification system that processes queries coming from camera-equipped mobile phones. Queries are in the form of colored images transmitted via the Multimedia Messaging Services (MMS) technology. Face localization is performed on each query image through the methods of skin color detection, region growing and ellipse analysis. A localized face region is represented as a set of features extracted through Kernel Principal Components Analysis. The features are submitted to Support Vector Machines for pattern classification. Recognition rates comparable with traditional systems demonstrate that it is possible to effectively implement a remote face recognition engine which takes as input the images captured by mobile phone cameras. Such an application, not limited by distance restrictions and readily accessible to any authorized person anywhere, exhibits strong potential in biometrics and security systems